2017
DOI: 10.1371/journal.pone.0182204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PNPLA3 and IFNL3 polymorphisms on hepatic steatosis in Asian patients with chronic hepatitis C

Abstract: Background and aimsA recent meta-analysis revealed that the genotype PNPLA3 rs738409 GG is associated with a higher risk of hepatic steatosis (HS) in Caucasian patients with chronic hepatitis C (CHC). However, controversial results were found regarding Asian populations. Furthermore, previous studies have shown a negative association between interferon lambda 3 (IFNL3) rs12979860 CC and HS in Caucasian CHC patients, but there have been no reports indicating any such association in Asian populations. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
1
6
0
2
Order By: Relevance
“…Previous studies found that PNPLA3 I148M is the most widely replicated genetic variant associated with increased hepatic steatosis [17-20, [74][75][76], and it has been observed that the GG genotype in CHC patients is associated with the greatest risk [21,22,24,54,62,[77][78][79][80]. In this study, we found that the mean CAP values of CAP steatosis stages among patients with CG and GG genotypes were significantly higher compared to those with CC genotype.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous studies found that PNPLA3 I148M is the most widely replicated genetic variant associated with increased hepatic steatosis [17-20, [74][75][76], and it has been observed that the GG genotype in CHC patients is associated with the greatest risk [21,22,24,54,62,[77][78][79][80]. In this study, we found that the mean CAP values of CAP steatosis stages among patients with CG and GG genotypes were significantly higher compared to those with CC genotype.…”
Section: Discussionsupporting
confidence: 54%
“…Meanwhile, Pirazzi et al demonstrated that PNPLA3 is highly expressed in human HSCs suggesting a potential link between HSCs, retinoid metabolism, and PNPLA3 in determining the susceptibility to hepatic fibrosis [83]. Discordant results were shown by Huang et al who found that the frequency of the rs738409 G allele was not significantly higher in CHC patients with advanced fibrosis (F3-F4 stages) than in patients with less advanced stages (F0-F2 stages) [80]. However, this result may have been related to the IFNL3 gene polymorphism, which is another factor associated with the severity of liver disease in CHC as other studies have explained [79,82].…”
Section: Discussionmentioning
confidence: 95%
“…When analyzing PNPLA3 polymorphisms, we found no association with liver steatosis or fibrosis in our cohort, despite other compelling data in this direction [ 24 , 25 , 39 41 ]. Huang et al (2017), found no significant association with the degree of liver fibrosis in 1,080 Asians with HCV [ 27 ]. Other studies have also found diverging results [ 26 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on chronic hepatitis C corroborate the relationship of this polymorphism with liver disease progression and steatosis [ 19 , 24 , 25 ]. However, other studies with a predominance of Asian populations have shown divergent results [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dawn of genome-wide association study (GWAS) approach highlighted the potential role of host genetic factors related to hepatic fat metabolism [including PNPLA3 (adiponutrin or patatin-like phospholipase domain-containing protein 3) and TM6SF2 (transmembrane 6 superfamily member 2) in CLP, mainly in nonalcoholic fatty liver disease (NAFLD) settings [5,6]. In this context, PNPLA3 rs738409 polymorphism has been found associated with liver fat content [7], as well as with clinical phenotypes of steatosis, steatohepatitis and liver fibrosis/cirrhosis in various hepatic etiologies of nonviral [mainly NAFLD and alcoholic liver disease (ALD)] [8,9] and viral (mainly CHC) [10,11] origins. Functionally, carriers of the G allele at the above-mentioned locus have a reduced enzymatic activity of adiponutrin, resulting in high levels of intracellular triglyceride [12], that may subsequently result in the higher predisposition to hepatic scarring and HCC [13].…”
Section: Introductionmentioning
confidence: 99%